Comparison of Carbon‐based Electrodes for Detection of Cresols in Voltammetry and HPLC with Electrochemical Detection. Issue 10 (14th July 2020) - Vosáhlová, Jana; Sochr, Jozef; Baluchová, Simona; Švorc, Ľubomír; Taylor, Andrew; Schwarzová‐Pecková, Karolina
Abstract: The electrochemical behavior of o ‐cresol and p ‐cresol was investigated using boron doped diamond (BDD) and sp 2 carbon‐based electrodes. BDD electrodes with different boron doping levels were used to optimize conditions for detection of cresols using differential pulse and square‐wave voltammetry. Comparable detection limits from 2.74 μM to 0.79 μM were achieved, using in‐situ anodic pretreatment to prevent fouling of electrode surface. Lower detection limits for cresols and other phenolic pollutants, in the 10 −7 M concentration range, were obtained using amperometric detection in HPLC. The proposed voltammetric and HPLC methods were utilized for determination of cresols in model river water samples. Abstract :